Reaction of Cytidine with Cyanopropargylic Alcohols: Synthesis of Functionalized Cytidine Cyclic Ketals - Nosyreva, Valentina V.; Mal’kina, Anastasiya G.; Volostnykh, Olga G.; Albanov, Alexander I.; Trofimov, Boris A. (Synthesis, 2013)
Cytidine reacts with one or two molecules of cyanopropargylic alcohols under mild conditions (K2CO3, DMF, 20–25 °C, 10–48 h) by the hydroxy groups of the ribose moiety to afford representatives of the two novel families of cytidine cyclic ketals. The first ones (53–76% yields) are formed with participation of the two vicinal hydroxyl groups (at 2′,3′-cis-positions) only. The second ones (7–21% yields) represent the adducts of cytidine with two molecules of cyanopropargylic alcohols involving all the three hydroxyl groups.
Keywords: cytidine; cyanopropargylic alcohols; nucleophilic addition; cyclization; cyclic ketals